OPTIMALISASI KETERAMPILAN BERBAHASA INGGRIS MELALUI PEMANFAATAN SOFTWARE PEMBELAJARAN BAHASA BAGI ANGGOTA KARANG TARUNA RT 01 RW 27 KADIPIRO SURAKARTA - Ulupi Sitoresmi; Sumardiono Sumardiono (Adi Widya : Jurnal Pengabdian Masyarakat, 2020)
This community service was conducted for Karang Taruna, a youth organnization, at Perum Graha Kencana RT 01 RW 27 Kadipiro Surakarta. The focus was a training of using Rosetta Stone and Google Translation to improve English skills. The materials were delivered using three phases namely presentation, practise, and production. The training was beneficial for the participants specifically to improve their listening, speaking, reading, and writing skills as well as translation. Having adequate understanding of using Rosetta Stone and Google Translation, the participants were able to develop their English especially when completing school assignments.Keywords: Rosetta Stone, Google Translation